Design and Implementation of a Floating PV Model to Analyse the Power Generation - Mohamad Reda A. Refaai; Lavanya Dhanesh; Bibhu Prasad Ganthia; Monalisa Mohanty; Ram Subbiah; Endalkachew Mergia Anbese (International Journal of Photoenergy)
The floating photovoltaic (FPV) system is a revolutionary power production technology that has gotten a lot of interest because of its many benefits. Aside from generating electricity, the technology can also prevent the evaporation of water. The electrical and mechanical structures of FPV power stations must be studied to develop them. Much research on FPV technologies has already been undertaken, and these systems have been evaluated from many perspectives. Many problems, including environmental degradation and electricity generation, fertile soils, and water management, are currently limiting societal growth. Floating photovoltaic (PV) devices save a great of land and water resources and have a greater energy conversion efficiency than standard ground power systems. A performance investigation of photovoltaic (PV) installations set on a moving platform is carried out. The paper presents and discusses various design alternatives for boosting the profitability and efficiency of floating photovoltaic (FPV) systems. Especially, FPV systems that take advantage of increasing capabilities like monitoring, conditioning, and attention were included. Although researchers have agreed on the benefits of floating systems, there has been little in-depth research on the parameters of floating photovoltaic systems. The results of this research tests were performed, and these reveal that the beneficial monitoring and conditioning impacts result in a significant gain in performance. The effects of using flat reflections on improvements are also investigated. As a result, this research examines the evolution of photovoltaic systems, then investigates the power generation capacity of floating photovoltaic systems, and then examines the benefits and possibilities of floating PV systems in depth. The concept of developing an integrated air storage system using a floating building on waters is discussed.